Advances in estimating the Phillips curve. Issue 1 (31st December 2022) - Guirguis, Hany; Suen, Tin Shan (Michael)
ABSTRACT: Many studies have documented the missing relationship between PCE inflation and the labor market slack in the last 20 years. This paper first presents evidence of a strong sensitivity of price inflation to labor market tightness once we remove the late 90s from our sample and account for the Phillips curve's endogeneity and nonlinearity. However, the Phillips curve can neither explain nor forecast the Core PCE inflation rate since 1995. This shortcoming is of great concern, given that the Fed utilizes the Core PCE as its primary tool to measure inflation and formulate its monetary policy. Second, we propose the Underlying Inflation Gauge (UIG) and the Median CPI to measure inflation better. We show that the Convex Phillips curve successfully explains and forecasts more than 90% of the UIG inflation movements from 1995:05 to 2019:03